Sulforaphane Inhibits Inflammatory Responses of Primary Human T-Cells by Increasing ROS and Depleting Glutathione - Liang, Jie; Jahraus, Beate; Balta, Emre; Ziegler, Jacqueline D.; Hübner, Katrin; Blank, Norbert; Niesler, Beate; Wabnitz, Guido H.; Samstag, Yvonne (Frontiers in Immunology, 2018)
The activity and function of T-cells are influenced by the intra- and extracellular redox milieu. Oxidative stress induces hypo-responsiveness of untransformed T-cells. Vice versa increased glutathione (GSH) levels or decreased levels of reactive oxygen species (ROS) prime T-cell metabolism for inflammation, e.g. in rheumatoid arthritis (RA). Therefore, balancing the T-cell redox milieu may represent a promising new option for therapeutic immune modulation. Here we show that sulforaphane (SFN), a compound derived from plants of the Brassicaceae family, e.g. broccoli, induces a pro-oxidative state in untransformed human T-cells of healthy donors or RA patients. This manifested as an increase of intracellular ROS and a marked decrease of GSH. Consistently, increased global cysteine sulfenylation was detected. Importantly, a major target for SFN-mediated protein oxidation was STAT3, a transcription factor involved in the regulation of TH17-related genes. Accordingly, SFN significantly inhibited the activation of untransformed human T-cells derived from healthy donors or RA patients, and specifically downregulated the the transcription factor RORt expression of the TH17-related cytokines IL-17A, IL-17F, and IL-22, which play a major role within the pathophysiology of many chronic inflammatory/autoimmune diseases. The inhibitory effects of SFN could be abolished by exogenous supplied GSH and the GSH replenishing antioxidant N-acetyl-cysteine (NAC). Together, our study provides mechanistic insights into the mode of action of the natural substance sulforaphane. It specifically exerts TH17 prone immunosuppressive effects on untransformed human T-cells by decreasing GSH and accumulation of ROS. Thus, SFN may offer novel clinical options for the treatment of TH17 related chronic inflammatory/autoimmune diseases such as rheumatoid arthritis.